2006
DOI: 10.1590/s0036-36342006000800008
|View full text |Cite
|
Sign up to set email alerts
|

La violencia en las mujeres usuarias de los servicios de salud en el IMSS y la SSA

Abstract: Violence in women with no social security is higher. Partner's alcohol intake pattern is an important risk factor. Detection of domestic violence in the clinical setting is necessary to recognize its real magnitude as a social problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
3
3
1
2
Order By: Relevance
“…Our findings on sexual violence are similar to those described by Vizcarra et al 23 and McCloskey et al 21 , who found a prevalence of 3.4% in the city of Temuco, in Chile, and 3% in Tanzania, respectively. Our findings also came close to the 7.5% described by Gómez-Dantés et al 24 in a study carried out in Mexico. The similarity of the results could be attributable to the cultural similarities of these countries, where power relations between men and women are very unequal.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings on sexual violence are similar to those described by Vizcarra et al 23 and McCloskey et al 21 , who found a prevalence of 3.4% in the city of Temuco, in Chile, and 3% in Tanzania, respectively. Our findings also came close to the 7.5% described by Gómez-Dantés et al 24 in a study carried out in Mexico. The similarity of the results could be attributable to the cultural similarities of these countries, where power relations between men and women are very unequal.…”
Section: Discussionsupporting
confidence: 92%
“…Violence against women has been widely studied in Brazil, although there are relatively few strongly associated with violence against women, supporting the results of Gómez-Dantés et al 24 , Klevens 36 , Rivera-Rivera et al 29 , and Menezes et al 13 . Several investigations of violence against women 13,23,36 including those conducted by the WHO 2 , present this variable as a risk factor for violence against women.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Os resultados desta pesquisa foram idênticos aos encontrados nos estudos realizados no México, em São Paulo-SP, na Zona da Mata de Pernambuco-PE e em Ribeirão Preto-SP. 16, Na pesquisa realizada no Serviço de Urgência e Emergência de Salvador-BA, foi encontrada a sequência de violência física psicológica e sexual. 22 Nos estudos de Florianópolis-SC e Fortaleza-CE apresentaram somente violência física.…”
Section: Introductionunclassified